Toxoplasma gondii Dense Granule Proteins 7, 14, and 15 Are Involved in Modification and Control of the Immune Response Mediated via NF-κB Pathway - Ihara, Fumiaki; Fereig, Ragab M.; Himori, Yuu; Kameyama, Kyohko; Umeda, Kosuke; Tanaka, Sachi; Ikeda, Rina; Yamamoto, Masahiro; Nishikawa, Yoshifumi (Frontiers in Immunology, 2020)
Toxoplasma gondii infects almost all warm-blooded animals, including humans, leading to both cellular and humoral immune responses in the host. The virulence of T. gondii is strain specific and is defined by secreted effector proteins that disturb host immunity. Here, we focus on nuclear factor-kappa B (NFκB) signaling, which regulates the induction of T-helper type 1 immunity. A luciferase assay for screening effector proteins, including ROPs and GRAs that have biological activity against an NFκB-dependent reporter plasmid, found that overexpression of GRA7, 14, and 15 of a type II strain resulted in a strong activity. Thus, our study was aimed at understanding the involvement of NFκB in the pathogenesis of toxoplasmosis through a comparative analysis of these three molecules. We found that GRA7 and GRA14 were partially involved in the activation of NFκB, whereas GRA15 was essential for NFκB activation. The deletion of GRA7, GRA14, and GRA15 in the type II Prugniaud (Pru) strain resulted in a defect in the nuclear translocation of RelA. Cells infected with the PruΔgra15 parasite showed reduced phosphorylation of inhibitor-κBα. GRA7, GRA14, and GRA15 deficiency decreased the levels of interleukin-6 in RAW246.7 cells, and RNA-seq analysis revealed that GRA7, GRA14, and GRA15 deficiency predominantly resulted in downregulation of gene expression mediated by NFκB. The virulence of all mutant strains increased, but PruΔgra14 only showed a slight increase in virulence. However, the intra-footpad injection of the highly-virulent type I RHΔgra14 parasites in mice resulted in increased virulence. This study shows that GRA7, 14, and 15-induced host immunity via NFκB limits parasite expansion.